Penyelesaian Wanprestasi Dalam Perjanjian Pembiayaan Haji Melalui Finance : (Studi Di FIF Group Cabang Praya) - Prastiwi Handani; H. Zaenal Arifin Dilaga; Rahmawati Kusuma (Private Law, 2023)
This study aims to look at the contractual relationships surrounding hajj financing at PT. Federal International Finance (FIF Group) Branch Praya, as well as how those agreements are resolved when there is a breach of contract, and what causes consumer breaches of contract. The study uses a normative-empirical legal research methodology and draws on three perspectives: conceptual, legal, and sociological. This study uses qualitative and descriptive analysis to examine legal texts. According to the study's findings, PT. Federal International Finance (FIF Group) Branch Praya’s consumer financing agreement governs the hajj financing, which is a component of a brand-named religious travel program. The study's findings suggest that PT. Federal International Finance (FIF Group) Branch Praya's consumer financing agreement governs the legal relationship for hajj financing, which is a component of a religious travel program offered by PT. Federal International Finance (FIF Group) with the brand name "AMITRA." In hajj financing agreements, the resolution of a breach of contract is accomplished using out-of-court procedures such discussion or mutual consultation between the parties. customers' poor economic conditions, deteriorating payment capacity, their death with recalcitrant heirs, their having several lending facilities, and the failure of consumer-owned firms are among the factors that contribute to contract breaches by customers.